Treatment-induced amenorrhoea for patients with HER2-positive early breast cancer: does it matter? - Gullo, Giuseppe; Gleeson, Jack P. (Translational Cancer Research, 2018)
The long-term outcome of patients with HER2-positive (HER2+) early breast cancer (EBC) has improved dramatically since the introduction of HER2-targeted therapies as part of the systemic standard of care (1-4). Consequently, survivorship issues, such as treatment related amenorrhoea (TRA) for younger patients, are increasingly important considerations for their impact on quality of life (QoL), however the prognostic implications of TRA remain unknown.